2023
DOI: 10.3389/fimmu.2023.1129746
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid function and associated mood changes after COVID-19 vaccines in patients with Hashimoto thyroiditis

Abstract: ContextSevere acute respiratory syndrome-coronavirus 2 (COVID-19) vaccines may incur changes in thyroid functions followed by mood changes, and patients with Hashimoto thyroiditis (HT) were suggested to bear a higher risk.ObjectivesWe primarily aim to find whether COVID-19 vaccination could induce potential subsequent thyroid function and mood changes. The secondary aim was to find inflammatory biomarkers associated with risk.MethodsThe retrospective, multi-center study recruited patients with HT receiving COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In TED, the hypothesized immune disruption following Covid-19 vaccination may be compared with that induced by radioiodine treatment, which triggers an immunological activation due to massive thyroid antigen release, with consequent increase in serum thyroid autoantibodies titers ( 64 ). Indeed, an increase in thyroglobulin autoantibodies, thyroid peroxidase autoantibodies, and autoantibodies stimulating the thyrotropin receptor has also been reported following Covid-19 vaccination ( 65 , 66 ), as well as changes in serum thyrotropin concentrations ( 67 ). As observed with the radioiodine-induced form, TED triggered by Covid-19 vaccination is not transient, has the same clinical characteristics as the spontaneous form, can present with all grades of severity, and has been approached with conventional treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In TED, the hypothesized immune disruption following Covid-19 vaccination may be compared with that induced by radioiodine treatment, which triggers an immunological activation due to massive thyroid antigen release, with consequent increase in serum thyroid autoantibodies titers ( 64 ). Indeed, an increase in thyroglobulin autoantibodies, thyroid peroxidase autoantibodies, and autoantibodies stimulating the thyrotropin receptor has also been reported following Covid-19 vaccination ( 65 , 66 ), as well as changes in serum thyrotropin concentrations ( 67 ). As observed with the radioiodine-induced form, TED triggered by Covid-19 vaccination is not transient, has the same clinical characteristics as the spontaneous form, can present with all grades of severity, and has been approached with conventional treatments.…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with previous reports of autoimmune hypothyroidism after a COVID vaccination [36] and another report of sub-acute thyroiditis occurring after vaccination with mRNA-based vaccines (68.7%), viral vector vaccines (15.7%), and 14.5% following inactivated vaccines [37]. A recent study enrolled 2765 patients and revealed that a COVID-19 vaccination seemed to induce increased levels of TSH followed by mood disturbance, and pre-vaccine serum TSH, CRP, and anti-TPO should be evaluated [38].…”
Section: Discussionmentioning
confidence: 99%